How to control the Indoor Environmental Quality through the use of the Do-It-Yourself approach and new pervasive technologies. (December 2017) - Salamone, Francesco; Belussi, Lorenzo; Danza, Ludovico; Ghellere, Matteo; Meroni, Italo
Abstract: The article describes the results of the "Open-source Smart lamp" aimed at designing and developing a smart appliance that integrates a wireless communication system for building automation, following the maker movement philosophy. The device is able to get an overview of the potential of a nearable device equipped with a variety of sensors to broadcast digital data for the management and control of the Indoor Environmental Quality (IEQ) of the built environment. The Smart Lamp installed in a real office in order to test the reliability of the device in the management of the lighting and air quality levels.